Hubungan Spiritual Quotient dengan Tingkat Stres pada Mahasiswa Kedokteran di Semarang - Irfandi, Nurahmat Yanisa; Widayati, Ratih; Fuad, Wijayanti (Jurnal Biomedika dan Kesehatan, 2024)
Background Student medical is one major favorite where his students are confronted with various relative constraints difficult to take, like many it's a mandatory academic target resolved and prosecuted adapt from transition high school to college sure height different from facet academic, then environment social making student stressed and triggered it happened stress.  stress will raise problems for students when not managed with ok. The spiritual Quotient (SQ) is one factor that plays a role in controlling stress. Students who have a High Spiritual Quotient will be capable of controlling stress. Methods Research this characteristic quantitative, observational analysis with an approach cross-sectional. The instrument used consists of a questionnaire from the level Spiritual Quotient with the title “questionnaire spiritual intelligence” and level stress with the title "MSSQ questionnaire" and well both have been already through validity and test reliability. The analysis study use analysis bivariate with the Rank Spearman correlation test. The sample study is student-level beginning Faculty Medical Unimus class of 2021 as many as 115 of the 150 students taken with the Simple Random Sampling technique. Results Connection significant (p=0.001) and strong correlation (r=0.568) between the connection Spiritual Quotient with level stress on Unimus FK Students Class of 2021. In part, students own High Spiritual Quotient in circumstances stress moderate (55.7%), stress weight (3.5%), and stress mild (0.9%). Conclusions Increasingly tall Spiritual Quotient possessed, than the more low-level stress experienced by students level beginning class of 2021.